Determination of the effect of impurity inclusions in the form of oxy-nitride phases in NiAl2O4 ceramics on resistance to high-temperature degradation during hydrogen saturation of near-surface layers - Gulnaz Zh Moldabayeva; Artem L. Kozlovskiy (Case Studies in Chemical and Environmental Engineering)
The degradation resistance growth of anode ceramic materials with the possibility of maintaining the stability of electrochemical and thermal conductivity properties under conditions of long-term high-temperature operation is one of the key directions in the development of solid oxide fuel cells. This article examines the possibility of modification of NiAl2O4 ceramics by adding aluminum nitride to them during the synthesis process, which leads to the formation of inclusions in the form of oxy-nitride grains. The interest in this class of ceramics is due to their structural features, which allows to consider them as one of the promising types of ceramics in the field of anode materials for solid oxide fuel cells. During assessment of the influence of impurity inclusions in the form of the oxy-nitride Al7O3N5 phase in the composition of NiAl2O4 ceramics on the deformation-induced swelling of the crystal structure of the damaged layer under high-dose irradiation, it was established that an elevation in the impurity phase concentration from 2.5 to 7.0 wt % results in swelling resistance growth by more than 4 times compared to NiAl2O4 ceramics without impurity inclusions. It was also determined that the presence of impurity inclusions in the composition of NiAl2O4 ceramics leads to a decrease in the coefficient of thermal volumetric expansion, a reduction of which indicates increased stability of the crystalline structure of ceramics to external temperature influences.